Ayurvedic Management of Garbhasravi Vandhya (International Journal of Ayurveda and Pharma Research, 2025)
Vandhyatwa is not only the inability to conceive but also the failure to produce a viable offspring. Garbhasravi vandhya is one among the six types of Vandhyatwa described in Harita Samhita. Ectopic gestations may result in Garbhasrava. An ectopic pregnancy is one in which the fertilized ovum is implanted and develops outside the normal endometrial cavity. Approximately 10-15% of couples, with various contributing factors like age, health conditions, and lifestyle choices suffer with Vandhyata. In the present case, a 27 year old married woman complaints of inability to beget a viable child even after 2 years of unprotected sexual life. She had history of 2 ectopic gestations 1 year apart. She came to our OPD for pre conceptional care and underwent IP management for 2 months. The case was managed through a combination of medications and procedures such Udwarthana, Choorna pinda sweda, Virechana and Matravasthi which were Srotosodhana, Agnideepana, and Vatakaphahara in properties. On discharge the patient was advised to take Vatasunga with milk for Puthrolpatha sthithi pradam (for conception and proper implantation of Garbha). The patient got conceived and delivered a full term live female baby through LSCS.